Customer-Oriented Classification:An Expert System Approach to Facet Analysis - Gopinath, M. A. (Journal of Information and Knowledge, 1998)
Analytico-synthetic approach to classification and information interfacing provides a helpful system of information access and use. The developments in the knowledge representation processes in rule-based systems provides an appropriate modelling for facet analysis of subjects. The advantage of this combination is presented.